2019
DOI: 10.1049/iet-map.2018.5599
|View full text |Cite
|
Sign up to set email alerts
|

Compact wearable MIMO antenna with improved port isolation for ultra‐wideband applications

Abstract: In this communication, a compact two‐element ultra‐wideband (UWB) wearable multiple‐input multiple‐output (MIMO) antenna with high port isolation is presented. The proposed structure is composed of jeans material in which an ‘8’ shaped stub is placed on the middle position of the antenna backside and connected to the partially suppressed ground structure to improve the port isolation characteristics. The antenna covers the frequency range from 2.74 to 12.33 GHz (about 127.27%) with the port isolation of >26 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Simulated and measured capacity loss are shown in Figure . The acceptable capacity loss for a MIMO system is less than <0.4 b/s/Hz, and it can be found that the proposed antenna provides capacity loss <0.1 b/s/Hz except at the notch band.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Simulated and measured capacity loss are shown in Figure . The acceptable capacity loss for a MIMO system is less than <0.4 b/s/Hz, and it can be found that the proposed antenna provides capacity loss <0.1 b/s/Hz except at the notch band.…”
Section: Resultsmentioning
confidence: 92%
“…Capacity Loss is a measure of channel capacity loss provided by a MIMO system. It is calculated by using the following equation: Closs=log2det()center1||S112+||S122S11*S12+S21*S12S22*S21+S12*S211||S222+||S212 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technology can immensely improve the channel capacity, data rate, and link safety of wireless systems by multi-path data communication [6]. These systems conduct the power through multiple antennas at the transmitter and receiver thereby enhancing the channel capacity without the use of supplementary bandwidth or power [7]. These systems are at present engaged in 4G user material and are a rising technology for service in the eventual 5G mobile terminals.…”
Section: Introductionmentioning
confidence: 99%